Two new species of Brachypeplus Erichson from India with a key to the Indian species (Coleoptera: Nitidulidae: Cillaeinae). (3rd April 2019) - Dasgupta, Jhikmik; Pal, Tarun Kumar
Abstract: Two new species of Brachypeplus [ viz ., B. rugisternus sp. n. and B. pallidus sp. n.] are described from Uttar Pradesh and the north-east Indian states of Assam and Arunachal Pradesh thereby increasing the number of Indian species to four. A key to the species of Brachypeplus from India is appended. http://www.zoobank.org/urn:lsid:zoobank.org:pub:9D084E6C-DB92-4CBD-A55C-C90D19E9BF7A